2006
DOI: 10.1111/j.1365-2265.2006.02707.x
|View full text |Cite
|
Sign up to set email alerts
|

A lesser postprandial suppression of plasma ghrelin in Prader–Willi syndrome is associated with low fasting and a blunted postprandial PYY response

Abstract: In PWS, the low decrease in postprandial ghrelin levels could be related to the low fasting PYY concentrations and their blunted postprandial response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 65 publications
2
38
1
4
Order By: Relevance
“…Despite overall higher levels of ghrelin in PWS, these subjects still exhibited normal postprandial suppression of ghrelin in our study, consistent with results reported in 3 studies of children with PWS (Haqq et al, 2003, Paik et al, 2006and Paik et al, 2007b and another of adults (Gimenez-Palop et al, 2007). Future trials are needed to elucidate the role of ghrelin in PWS using specific ghrelin antagonists, currently in development.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite overall higher levels of ghrelin in PWS, these subjects still exhibited normal postprandial suppression of ghrelin in our study, consistent with results reported in 3 studies of children with PWS (Haqq et al, 2003, Paik et al, 2006and Paik et al, 2007b and another of adults (Gimenez-Palop et al, 2007). Future trials are needed to elucidate the role of ghrelin in PWS using specific ghrelin antagonists, currently in development.…”
Section: Discussionsupporting
confidence: 90%
“…Some have found that adults and children with PWS have lower fasting and postprandial PYY levels than controls (Butler et al, 2004 andGimenez-Palop et al, 2007), while others reported no difference (Goldstone et al, 2005 andPaik et al, 2007a) or increased PYY levels (Bizzarri et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…26,27,32,34,36 --38,40,43 --48 Levels of ghrelin do fall after food intake in children and adults with PWS but remain elevated compared with the controls relative to their obesity. 37,38,40,43,44 In our current study, we were unable to demonstrate any elevation of plasma ghrelin levels in PWS children under 5 years, unadjusted or when correcting for age, BMI, fasting insulin or insulin resistance. This finding is in agreement with previous studies of PWS children aged under 3 or 5 years, 39,42,46 although it should be noted that one of these studies did not find hyperghrelinaemia in PWS children over 3 years and adults either.…”
Section: Ghrelincontrasting
confidence: 80%
“…( Bizzarri et al, 2010;Cummings et al, 2002b;Gimenez-Palop et al, 2007;Goldstone et al, 2005;Haqq et al, 2003a;Paik et al, 2004). Levels of fasting ghrelin may also even be higher in PWS patients than in lean controls (Bizzarri et al, 2010;Choe et al, 2005a;Cummings et al, 2002b;Delparigi et al, 2002;Gimenez-Palop et al, 2007).…”
Section: Ghrelin and Prader-willi Syndromementioning
confidence: 99%
“…Levels of fasting ghrelin may also even be higher in PWS patients than in lean controls (Bizzarri et al, 2010;Choe et al, 2005a;Cummings et al, 2002b;Delparigi et al, 2002;Gimenez-Palop et al, 2007). Postprandial levels of ghrelin do fall in patients with PWS though they remain elevated compared to non-PWS obese controls, with conflicting results as to whether the magnitude of the decrease in ghrelin is blunted (Gimenez-Palop et al, 2007;Goldstone et al, 2005;Haqq et al, 2003b). In addition, the age-related decline in ghrelin is blunted in PWS infants and children (Haqq et al, 2008).…”
Section: Ghrelin and Prader-willi Syndromementioning
confidence: 99%